PENERAPAN LAYANAN KONSELING INDIVIDU DALAM MENGATASI KESULITAN MENGEMUKAKAN PENDAPAT BAGI SISWA - Arsaudi, Arsaudi (STKIP Andi Matappa, 2017)
The aim of the study is to determine (1) how the picture of the difficulties students express their opinions in SMP Negeri 1 Segeri ?, (2) what factors cause difficulty expressing their opinions on students of SMP Negeri 1 Segeri? (3) how the picture of the implementation of individual counseling services to help mnegatasi difficulty expressing their opinions on students of SMP Negeri 1 Segeri ?. Case study in two children who experienced trouble expressing their opinions. Data analysis, namely: Data reduction, data display and Conclusion Drawing / verification. Results (1) difficulty expressing their opinions on students such as; aspects of personality, learning aspect, the social aspect. (2) The factors causing difficulty expressing their opinions consist of internal factors such as feelings of shame or fear of making mistakes, lack of speech, lack of preparation, low self-esteem, physical deficiencies, trauma, felt unable to express an opinion, do not consider important the opportunity to express opinions, and fear that is excessive if expression .; and external factors such as a lack of social support, lack of respect and attention, lack of means of support for freedom of expression, lack of motivation from the family and the environment, and the absence of an opportunity to express opinions; (3) Results of interview counseling individuals who demonstrate the changes and development of US students and AL in some aspects such as changes to the enthusiasm of students in participating layananan individual counseling, the openness of the students in presenting the issues, the development of the ability to identify weaknesses and strengths in an effort to solve this problem, and the development of students' abilities in overcoming difficulties experienced expression.